Spirituality and Information Technologies: Their Influence on the Consciousness of Modern Youth - Irnazarova Sevinch (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the role of information technologies in modern society and their positive and negative impact on the spiritual development of young people. Special attention is given to the importance of spiritual education in the digital environment, the formation of information culture, and the role of family, education, and society in shaping the younger generation. The article also analyzes the rational use of information technologies for raising spiritually mature, educated, and modern youth.